Genesis of national legislation and scientific thought development regarding criminal liability for perjury - K. A. Romanauskas (Bulletin of Kharkiv National University of Internal Affairs)
One of the ways to mislead a court or other authorised body is to provide deliberately false testimony by a witness or victim, for which the legislator provides for criminal liability in Article 384 of the Criminal Code of Ukraine. Based on the social danger of this criminal offence, which is an encroachment on the lawful procedure for the administration of justice, in particular, ensuring the rule of law, legality in the procedural activities of courts, law enforcement agencies, and other institutions entrusted with the enforcement of court decisions, the importance of ensuring a high-quality investigation of these criminal offences has been emphasised. The purpose of the study is defined as clarification and generalisation of theoretical concepts of the emergence and historical development of the peculiarities of criminal liability for knowingly false testimony of a witness and a victim, and outlining the areas for improvement of modern scientific knowledge on this issue.